2013
DOI: 10.2478/s11535-013-0255-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PRP and PPP on proliferation and migration of human chondrocytes and synoviocytes in vitro

Abstract: Cartilage tissue engineering can provide substantial relief to people suffering from degenerative cartilage disease, such as osteoarthritis. The autologous platelet-rich plasma (PRP) application appears to improve cartilage healing due to its ability to positively influence cellular mechanisms, mainly in cells from synovium and cartilage. Primary cultures of human synovial fluid stem cells (synoviocytes, SCs) and chondrocytes (CCs) were exposed to various concentrations of non-activated PRP and plateletpoor pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
4
9
0
Order By: Relevance
“…In the scratch wound healing assay, PRFM at different concentrations (50% and 100%) could induce significant meniscocyte migration in culture similar to FBSM. In the transwell migration assay, normal PRF could successfully induce significant meniscocytes migration in culture, as that of PRP reported previously [ 38 ]. The growth factors and chemokines originating from PRF enhance the migration of meniscocytes [ 38 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the scratch wound healing assay, PRFM at different concentrations (50% and 100%) could induce significant meniscocyte migration in culture similar to FBSM. In the transwell migration assay, normal PRF could successfully induce significant meniscocytes migration in culture, as that of PRP reported previously [ 38 ]. The growth factors and chemokines originating from PRF enhance the migration of meniscocytes [ 38 ].…”
Section: Discussionsupporting
confidence: 67%
“…In the transwell migration assay, normal PRF could successfully induce significant meniscocytes migration in culture, as that of PRP reported previously [ 38 ]. The growth factors and chemokines originating from PRF enhance the migration of meniscocytes [ 38 ]. Our results are comparable to other studies that showed the effects of fetal bovine serum on cell migration and the proliferation of porcine meniscal cells in microwound and repair models.…”
Section: Discussionsupporting
confidence: 67%
“…Collagenase type II used in our study did not impair the detection of the CD90, CD44 and CD45 markers. We have confirmed expression of the hyaluronan receptor CD44 and CD 90 (Thy-1) on chondrocytes (1P) as was previously reported (14,15,16). The hyaluronan receptor CD44 belongs to the polymorphic family of CD44 glycoproteins, which have been implicated in a variety of cellular functions including adhesion to hyaluronan and collagen, and which is present in normal chondrocytes (15).…”
Section: Discussionsupporting
confidence: 90%
“…8 The growth factors and chemokines originating from PRF enhance the migration of chondrocytes. 2 An ex vivo explant culture model mimicking in vivo microenvironment also confirmed the ability of cellular migration in the tissue level. Cell outgrowth was noted from the minced tissue fragments, and adherence of chondrocytes onto the porous PRF scaffold was observed thereafter.…”
Section: Discussionmentioning
confidence: 68%